The effect of hydroxyapatite nanoparticles on wettability and brine-oil interfacial tension as enhance oil recovery mechanisms - Ngouangna, Eugene Ngwana; Mohd Zaidi, Jaafar; Mohammadnoorul Noorul Anam, Mohd Norddin; Agi, Augustine Aja; Abdul Rahim, Risal; Chinedu Mamah, Stanley Chinedu; Oseh, Jeffrey Onuoma (Elsevier B.V., 2022)
A novel concept of utilizing nanoparticles (NPs) to boost oil recovery and reduce entrapped oil in hydrocarbon reservoirs is being explored. The use of nanofluids (NFs) flooding to change wettability and reduce interfacial tension (IFT) between oil and water has been shown to be highly effective in experiments. Preparation and modification methods influence the performance of NPs. The application of hydroxyapatite NPs (HAP) in EOR has yet to be investigated. HAP was synthesized in this study using the co-precipitation method and in-situ surface functionalization with Sodium Dodecyl Sulphate SDS to visualize it effect on IFT reduction and wettability alteration under different salinity and temperature settings. To confirm the synthesis of HAP, zeta potential (ZP), Fourier transform infrared spectroscopy (FTIR), Particle size analysis (PSA), Transmission electron microscopy (TEM), and Energy dispersive X–ray (EDX) spectra were used respectively. According to the results, HAP was produced, and the particles were finely distributed and stable in aqueous solution. When the pH was altered from 1 to 13, the particles' surface charge rose from -5mV to −27mV, showing long-term stability in EOR processes. At salinity range from 5000 ppm to 30,000 ppm, and under temperature range from 25ᵒC to 80ᵒC, the HAP NFs changed the wettability of sandstone core from oil–wet at 111.7° to water–wet at 9.0°. In addition, at 0.1 wt% HAP concentration, the IFT was lowered to 3 mN/m. As a result, the HAP NF proved very effective in reducing IFT and altering wettability under both low and high salinity environments, and it is thus suggested for EOR operations.